Light Quality Environment and Photomorphological Responses of Young Olive Trees - Ladux, Federico J.; Trentacoste, Eduardo Rafael; Searles, Peter Stoughton; Rousseaux, María Cecilia (MDPI, 2022)
Tree densities have increased greatly in olive orchards over the last few decades. In many annual crop species, increased density reduces the horizontal red/far-red (R/FR) and blue/green (B/G) ratios during canopy development even before direct shading occurs, and such changes are known to alter plant morphology. This study with olive trees evaluated: (1) whether the leaf area index (LAI) of neighboring trees modifies the light quality environment prior to a tree being directly shaded and (2) the potential morphological responses of three olive cultivars to changes in light quality. Increasing LAI using different spatial arrangements of potted, three-year-old trees reduced the horizontal R/FR ratio more than that of the B/G ratio. Cultivar-specific responses to low R/FR ratio were observed for individual leaf area and aboveground/belowground biomass ratio using laterally positioned FR mirrors or green fences. No statistically significant responses were detected in response to green vegetation fences that reduced both horizontal R/FR and B/G ratios, but a cluster analysis grouped together the overall morphological responses to both FR mirrors and green fences. These results in olive trees suggest that cultivar differences in response to light quality may be relevant for understanding adaptation to dense orchards and identifying cultivars best suited to them.